Over-the-Air Testing of Cognitive Radio Nodes in a Virtual Electromagnetic Environment. (5th August 2013) - Sharma, Rajesh K.; Kotterman, Wim; Landmann, Markus H.; Schirmer, Christopher; Schneider, Christian; Wollenschläger, Frank; Del Galdo, Giovanni; Hein, Matthias A.; Thomä, Reiner S.
Abstract : This paper provides an overview of ongoing research in over-the-air (OTA) testing for next-generation communication and data transmission devices with special consideration of cognitive radio (CR). Existing state-of-the-art techniques and their merits and limitations are discussed. We identify the requirements and issues for the OTA test in a virtual electromagnetic environment (OTA in VEE) which needs to address the more complex scenario of future networks, where interference emulation becomes a highly challenging task. A complex interference scenario arises due to the attempt to simultaneously utilize several opportunity dimensions such as frequency, time, direction (space), and polarization, in a dynamic manner in a multiuser scenario. Although MIMO-OTA testing addresses many limitations of single antenna-conducted test systems, more dimensions and parameters to be addressed in the new scenarios imply further increase in cost and complexity. Closed-loop OTA test setups for CR evaluation are discussed along with an overview of other test scenarios.